Diagnosing Fish Bone and Chicken Bone Impactions in the Emergency Department Setting: Measuring the System Utility of the Plain Film Screen. (August 2015) - Devarajan, Karthik; Voigt, Stanley; Shroff, Sunil; Weiner, Scott G.; Wein, Richard O.
Objectives: In the emergency department, fish and chicken bone impactions are typically evaluated with screening x-rays. We sought to determine whether this modality ultimately improves system outcomes, including length of stay (LOS), cost, and radiation dosage. Methods: We reviewed patients ≥18 years old presenting to an urban academic emergency department over a 4-year period who received a screening soft-tissue x-ray to determine the presence of a retained fish or chicken bone. We calculated the diagnostic accuracy of x-ray and computed tomography (CT) evaluations, respectively, in addition to system outcomes. Results: Twenty-seven of the 78 patients included for analysis were ultimately positive for bone impaction. Initial x-ray interpretations demonstrated a sensitivity of 24.0% (95% CI, 9.4%-45.1%) and a specificity of 90.0% (95% CI, 78.2%-96.7%). However, initial CT interpretation (ie, a preliminary read from on-call residents) demonstrated a sensitivity of 75% (95% CI, 19.4%-99.4%) and a specificity of 100% (95% CI, 59.0%-100%). LOS, cost, and radiation dosage were not significantly different between patients who ultimately had true bone impactions and those who did not ( P > .05). Conclusions: X-rays are poor screening tools in determining fish or chicken bone impactions with poor diagnostic and system utility. Further studies should be performed to evaluate the role of a low-radiation CT screen.